Building Resilience through Nature-based Solutions: Exploring the Urban-Rural Linkages in Flood Mitigation Strategies for Jayapura - Christiana, Dominika Wara; Pribadi, Yudhistira S; Wihanesta, Retno (Smart City, 2023)
Nature-based solutions (NbS) offer flexibility and adaptability to different adoption scales and purposes. NbS adoption is influenced by various factors in the target area, including environmental, socio-cultural, and economic factors. Therefore, the chances of successful NbS adoption vary between locations due to different characteristics of the target area. This study aims to identify various factors influencing the suitability level of NbS adoption, potential locations for NbS adoption, and to assess urban-rural linkage in improving the water resilience of Jayapura. This research paper explores the potential locations for implementing nature-based solutions (NbS) in both urban and rural areas of Jayapura City. The NbS measures assessed in this study are landscape restoration, water storage pond, and multifunction green open space. This study employed the Analytical Hierarchy Process (AHP), a Multi-Criteria Decision Analysis (MCDA), to summarize the influence of six factors on suitability level. The result reveals that 75% of the Jayapura City area is highly suitable for landscape restoration interventions, especially in areas with lower population density. Whereas in urban areas, implementing multifunction green open spaces and water storage ponds can target flood reduction on a local scale. Building a city's resilience requires implementing NbS in both urban and rural areas. The paper highlights the importance of collaboration and coordination between urban and rural areas in enhancing the city's resilience.